ANALISIS PARAMETER KINERJA UNIT PEMBANGKIT LISTRIK TENAGA UAP SULUT-3 - Kumendong, Christovel; Arungpadang, Tritiya; Mende, Jefferson (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2023)
10Along with the increasing population and technological advances, so The need for electrical energy is also increasing so that it demands the availability of energy continuous electricity. One of the problems faced by PLTU North Sulawesi-3 2x50 MW as a supplier of electrical energy is a decline in performance generating unit caused by the Coal Feeder equipment experiencing disturbance. From these problems, an analysis is needed to find out how influential Coal Feeder equipment has on performance generator. The research was conducted by observing the work of the Coal Feeder on load, plant operation data processing based on Performance Index Formula PT PLN 2007 generator. From the results of the analysis, it can be concluded that: Coal Feeder operation plays an important role in the reliability and efficiency of the process power generation of PLTU Sulut-3 2x50 MW, so that if the Coal Feeder is disturbed it will affect performance generators such as low Equivalent Availability Factor (EAF) and High Equivalent Forced Outage Rate (EFOR). Keywords : Power Plant Performance , Coal Feeder